2014
DOI: 10.1098/rsfs.2014.0022
|View full text |Cite
|
Sign up to set email alerts
|

Phase-locked spiking of inner ear hair cells and the driven noisy Adler equation

Abstract: The inner ear constitutes a remarkably sensitive mechanical detector. This detection occurs in a noisy and highly viscous environment, as the sensory cells—the hair cells—are immersed in a fluid-filled compartment and operate at room or higher temperatures. We model the active motility of hair cell bundles of the vestibular system with the Adler equation, which describes the phase degree of freedom of bundle motion. We explore both analytically and numerically the response of the system to external signals, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
(65 reference statements)
4
14
0
Order By: Relevance
“…The addition of an offset term leads to a time-dependent modulation of the barrier height. It was shown that such a model leads to the occurrence of spikes, which can be entrained by a weak signal (31). Our data confirm the existence of spikes, and show that this entrainment occurs at extremely weak signals, before any effects on spike amplitude or rate are observed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The addition of an offset term leads to a time-dependent modulation of the barrier height. It was shown that such a model leads to the occurrence of spikes, which can be entrained by a weak signal (31). Our data confirm the existence of spikes, and show that this entrainment occurs at extremely weak signals, before any effects on spike amplitude or rate are observed.…”
Section: Discussionsupporting
confidence: 88%
“…The characteristics of spiking behavior shown here are consistent with theoretical studies of hair bundle motility (18,31). In a recent study, hair cell motion was modeled with a time-dependent Adler equation, which describes a system moving in a tilted washboard potential.…”
Section: Discussionsupporting
confidence: 82%
“…In the absence of noise, the phase is trapped in a potential well at high coupling, 3δω/ε < 1, and slides down the corrugated energy landscape at low coupling 33 . This qualitatively describes the phase-locking observed for contra-rotating rotors, for which δω ~ 0, and the slow revolution at Ω of co-rotating pairs, for which δω ~ 2ω.…”
Section: Lettersmentioning
confidence: 99%
“…4d). The presence of noise therefore helps the ensemble to encode high frequencies, analogous to stochastic resonance predicted for individual hair bundles38. Extracting the intensity of physiological noise from our data, and comparing it to results of the simulations, we found that the innate biological noise is in the range that offers a compromise between the enhancement of detection of high frequencies and maintaining the detection of low frequencies (see SI.…”
Section: Resultsmentioning
confidence: 57%
“…Variation of internal control parameters poises hair cells near different bifurcations, leading to different phase-locking characteristics133638. Hair bundle exhibits a regime of spontaneous limit cycle oscillation15, the frequency of which reveals an internal time scale defined by the active processes within the bundle.…”
Section: Discussionmentioning
confidence: 99%